2013
DOI: 10.1063/1.4828712
|View full text |Cite
|
Sign up to set email alerts
|

Fano resonances of microwave structures with embedded magneto-dipolar quantum dots

Abstract: Articles you may be interested inSize dependent ferromagnetic resonance and magnetic anisotropy of hexagonal barium and strontium ferrite powders J. Appl. Phys. 113, 17E154 (2013); 10.1063/1.4801742 Fano antiresonance in electron transport through a parallel-coupled quantum-dot structure Transition between onion states and vortex states in exchange-coupled Ni -Fe ∕ Mn -Ir asymmetric ring dots J. Appl. Phys. 99, 08G303 (2006); 10.1063/1.2164435 Mesoscopic effects in quantum dots, nanoparticles and nuclei AIP Co… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
36
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(37 citation statements)
references
References 47 publications
1
36
0
Order By: Relevance
“…Long radiative lifetimes of topologically singular MDMs combine strong subwavelength confinement of electromagnetic energy with a narrow spectral line width and may carry the signature of Fano resonances [39 -41]. It was shown [42] that interaction of the MDM ferrite particle with its environment has a deep analogy with the Fano-resonance interference observed in natural and artificial atomic structures. The aim of the present study is to show how the transition between symmetric Lorentzian and asymmetric Fano line shapes in microwave structures with MDM ferrite disks can be used for effective microwave spectroscopy.…”
Section: Introductionmentioning
confidence: 99%
“…Long radiative lifetimes of topologically singular MDMs combine strong subwavelength confinement of electromagnetic energy with a narrow spectral line width and may carry the signature of Fano resonances [39 -41]. It was shown [42] that interaction of the MDM ferrite particle with its environment has a deep analogy with the Fano-resonance interference observed in natural and artificial atomic structures. The aim of the present study is to show how the transition between symmetric Lorentzian and asymmetric Fano line shapes in microwave structures with MDM ferrite disks can be used for effective microwave spectroscopy.…”
Section: Introductionmentioning
confidence: 99%
“…Specific long-distance topological properties of these fields are exhibited in the effects of path-dependent interference [22]. It was also shown that interaction of the MDM ferrite particle with its environment has a deep analogy with the Fano-resonance interference observed in natural and artificial atomic structures [23]. A ferrite is a magnetic dielectric with low losses.…”
Section: Introductionmentioning
confidence: 99%
“…An example of such a spectrum, studied in Ref. [23], is shown in Figure 2. The resonance modes are designated in succession by numbers n = 1, 2, 3, .…”
Section: Energy Eigenstates Of Mdm Oscillations In a Quasi-2d Ferritementioning
confidence: 99%
See 2 more Smart Citations